Development of SSR markers related to salinity resistance based on transcriptomic sequences in Medicago sativa - Rugang Yu; Xin Chen; Hui Zhang; Qiting Zhang; Xinyi Chen; Yanqiu Dong; Liwei Chen; Daniel Basigalup; Guoliang Wang; Xueling Du (PLoS ONE, 2025)
Alfalfa ( Medicago sativa ) is an important perennial forage crop that exhibits wide cultivar variations in salinity tolerance. Simple sequence repeats (SSRs) in a transcriptome can realize targeted markers that are directly related to target traits. However, SSR markers related to specific traits, especially salinity tolerance traits in alfalfa, are rarely reported worldwide. This study aimed to investigate the distribution characteristics of SSR loci and explore the key SSR loci related to salinity-tolerant genes in alfalfa. For this purpose, we conducted transcriptomic analysis of roots and leaves from GIB (G, high salinity-tolerant) and LS (L, high salinity-sensitive) plants under 0 and 200 mM NaCl treatments, which yielded 129,563 unigenes. A total of 38,370 SSR loci were identified and distributed in 28,039 unigenes, and the frequency of SSR occurrence in each locus was 4.43 kb. Among all the SSR motifs, mononucleotide (67.32%), trinucleotide (15.61%), and dinucleotide (14.53%) were the major repeated types, and the forms of A/T, AG/CT, AAG/CTT, AC/GT, AT/AT and AAC/GTT were the most frequent motifs. Meanwhile, 23,159 primer pairs of SSRs were designed for marker development in alfalfa. Among the 28,039 SSR-containing unigenes, 1,947 unigenes were found to be salinity-responsive differentially expressed unigenes (DEUs) and/or DEUs between the two cultivars. Interestingly, 188 DEUs were identified and found to be involved in ion transport, metabolite biosynthesis, ROS regulation, signaling pathway, and transcription regulation, which were all related to salinity tolerance. Notably, six out of 211 SSR loci identified based on 188 SSR-containing DEUs were validated as polymorphic SSR markers with clear amplified bands, which they exhibited high polymorphism (polymorphism information content: 0.640–0.807). Therefore, these SSR markers could be further used for authenticity identification and genetic analysis. The six SSRs were used to classify four alfalfa varieties with different salinity tolerance into three groups. The high salinity-sensitive variety LS was placed in group I, the high tolerant varieties GIB and GN5 formed group II, and the sensitive variety GN3 was included in group III. This grouping was consistent with prior evaluations of salinity tolerance. Therefore, the six SSRs may be associated with salinity tolerance in alfalfa. These findings not only provide an efficient tool for the large-scale development of markers related to specific traits but also lay a foundation for genetic analysis in alfalfa.